2016
DOI: 10.1038/ncomms11290
|View full text |Cite|
|
Sign up to set email alerts
|

T-cell activation is an immune correlate of risk in BCG vaccinated infants

Abstract: Vaccines to protect against tuberculosis (TB) are urgently needed. We performed a case–control analysis to identify immune correlates of TB disease risk in Bacille Calmette–Guerin (BCG) immunized infants from the MVA85A efficacy trial. Among 53 TB case infants and 205 matched controls, the frequency of activated HLA-DR+ CD4+ T cells associates with increased TB disease risk (OR=1.828, 95% CI=1.25–2.68, P=0.002, FDR=0.04, conditional logistic regression). In an independent study of Mycobacterium tuberculosis-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
275
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(298 citation statements)
references
References 39 publications
14
275
1
Order By: Relevance
“…In areas with a high incidence of TB, even a small increase in the rate of HIV acquisition would have a major impact on pediatric HIV infections. Importantly, a recently published study reported that higher frequencies of activated CD4 ϩ T cells in BCG-vaccinated human infants from the MVA85A TB vaccine trial had an increased risk for TB disease (82). This is the first report that CD4 ϩ T cell activation is associated not only with higher HIV infection risk but also with predisposition to TB disease.…”
Section: Trained Immunity and Immune Activation Of Tb Vaccinesmentioning
confidence: 71%
“…In areas with a high incidence of TB, even a small increase in the rate of HIV acquisition would have a major impact on pediatric HIV infections. Importantly, a recently published study reported that higher frequencies of activated CD4 ϩ T cells in BCG-vaccinated human infants from the MVA85A TB vaccine trial had an increased risk for TB disease (82). This is the first report that CD4 ϩ T cell activation is associated not only with higher HIV infection risk but also with predisposition to TB disease.…”
Section: Trained Immunity and Immune Activation Of Tb Vaccinesmentioning
confidence: 71%
“…Although both CD4+ T cells and IFN-γ are required for control of M. tuberculosis infection (Flynn et al, 1993; Green et al, 2013), it has been difficult to establish whether these factors are sufficient to establish protective immunity (Kagina et al, 2010; Fletcher et al, 2016). Recently, the recombinant vaccine strain Modified Vaccinia Ankara virus expressing Ag85A (MVA85A) became the first new TB vaccine candidate to be tested for efficacy in infants in a clinical trial since BCG (Tameris et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…BCG-specific CD4 + , CD8 + and γδ T-cell expression of IFN-γ, TNF-α, IL-2, and IL-17 do not seem to correlate with the protection conferred by BCG in infants [111]. However in a more recent study, BCG-specific ELISPOT responses are associated with a reduced risk of disease in BCG-vaccinated South African infants [37]. BCG-specific T-cell ELISPOT antigen specific CD4 + T-cells do not appear to localize to the site of infection in lung tissue until 18–20 days after the establishment of disease, showing that M.tb delays the onset of adaptive Th1 immunity [112].…”
Section: Introductionmentioning
confidence: 89%
“…Recently, higher titres of IgG against Ag85A have been shown to associate with reduced risk of developing active disease in an infant case-control study [37]. This raises the possibility that anti-mycobacterial antibodies assist in the containment of initial infection with M.tb in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation